2008
DOI: 10.1055/s-0028-1083277
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Amidation of Carboxylic Acids Revisited

Abstract: Factors affecting the thermal condensation of carboxylic acids with amines have been investigated, and an effective protocol for this waste-minimized, environmentally benign transformation has been identified. Fourteen examples demonstrate the applicability of this procedure to aliphatic, aromatic and heteroaromatic carboxylic acids and primary and secondary aliphatic as well as aromatic amines. The approach leads to the corresponding amides in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 15 publications
2
58
0
1
Order By: Relevance
“…[13] During optimisation of this method it was observed that molecular sieves were not necessary for good conversion, although they were still employed in order to limit any pressure buildup in the sealed reaction vessel. [13] During optimisation of this method it was observed that molecular sieves were not necessary for good conversion, although they were still employed in order to limit any pressure buildup in the sealed reaction vessel.…”
Section: Amidation Of Carboxylic Acidsmentioning
confidence: 99%
“…[13] During optimisation of this method it was observed that molecular sieves were not necessary for good conversion, although they were still employed in order to limit any pressure buildup in the sealed reaction vessel. [13] During optimisation of this method it was observed that molecular sieves were not necessary for good conversion, although they were still employed in order to limit any pressure buildup in the sealed reaction vessel.…”
Section: Amidation Of Carboxylic Acidsmentioning
confidence: 99%
“…After finding the optimal reaction conditions, we studied the methodology with an array of commercially available aromatic and aliphatic carboxylic acids with benzylamine (Table 3, entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In comparison, aromatic carboxylic acids with electron deficient substituents were successfully reacted with benzylamine very rapidly than electron-rich aromatic carboxylic acids (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…7 In this regard, carboxamides and sulfonamides were prepared by the reaction of carboxylic and sulfonic acid derivatives with aromatic and aliphatic amines in the presence of SOCl 2 , 8 POCl 3 , 9 PCl 5 , 10 or SO 2 Cl 2 . 11 Also, amidation of carboxylic and sulfonic acids, have been reported by using cyanuric chloride, 12 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 4 carbodiimides, 13 uronium salts, 14 triphosgene, 15 PPh 3 /Cl 3 CN, 16 PPh 3 /SO 2 Cl 2 , 17 as acid activators.…”
Section: Introductionmentioning
confidence: 99%
“…Alkyd resin solution (90% solid) was taken in four-necked reaction kettle fitted with thermometer, stirrer and nitrogen gas inlet. Requisite quantity of 1,10-phenanthroline-5-amine was added and the temperature was maintained at 190-200 • C under nitrogen atmosphere [20]. Water condensed during reaction was removed by using Dean-Stark assembly.…”
Section: Modification Of Alkyd Resin With Phenanthrolinementioning
confidence: 99%